Promoting learner autonomy through teacher-student partnership assessment in an american high school: a cycle of action research (2012)
In this article I present some findings of an action research study intended to find out to what extent a teacher-student partnership in writing assessment could promote high school students’ autonomy. The study was conducted in a U.S. school. Two main action strategies in the assessment process were the use of symbols as the form of feedback and the design of a rubric containing criteria negotiated with the students as the scoring method. Results showed that the students developed some autonomy reflected in three dimensions: ownership of their learning process, metacognition, and critical thinking, which positively influenced an enhancement of their writing skills in both English and Spanish. Likewise, the role of the teacher was found to be paramount to set appropriate conditions for the students’ development of autonomy. En este artículo presento hallazgos de una investigación-acción cuyo objetivo era averiguar en qué medida una forma alternativa de evaluación negociada promovería la autonomía de los estudiantes. El estudio se realizó en una escuela secundaria norteamericana. Las principales estrategias de acción fueron el uso de símbolos en la retroalimentación y la inclusión de criterios negociados con los estudiantes en el diseño de una rúbrica que se utilizó como instrumento de evaluación y calificación. Los resultados mostraron que los estudiantes desarrollaron su autonomía en tres dimensiones: apropiación de su proceso de aprendizaje, metacognición y pensamiento crítico, lo que influenció positivamente el desarrollo de sus habilidades de escritura tanto en inglés como en español. Asimismo se encontró que el papel del profesor es de vital importancia para establecer condiciones propicias en el desarrollo de la autonomía de los estudiantes.